A fuzzy rough number extended AHP and VIKOR for failure mode and effects analysis under uncertainty. (January 2022) - Zhu, Guo-Niu; Ma, Jin; Hu, Jie
Abstract: Failure mode and effects analysis (FMEA) is one of the most popular reliability analysis techniques due to its outstanding capabilities in identifying, assessing, and eliminating potential failure modes in a wide range of industrial applications. It provides a comprehensive view for investigating potential failures, causes, and effects in designs, products, and processes. However, traditional FMEA is extensively criticized for its defects in determining the criteria weights, identifying the risk priority of failure modes, and handling the uncertainty during the risk evaluation. To resolve these problems, this study proposes a novel fuzzy rough number extended multi-criteria group decision-making (FR-MCGDM) strategy to determine a more rational rank of failure modes by integrating the fuzzy rough number, AHP (analytic hierarchy process), and VIKOR (Serbian: VIseKriterijumska Optimizacija I Kompromisno Resenje). Above all, a fuzzy rough number is introduced to characterize experts' judgment, aggregate group risk assessments, and tackle the uncertainty and subjectivity in the risk evaluation. Then a fuzzy rough number enhanced AHP is presented to determine the criteria weights. A fuzzy rough number enhanced VIKOR is proposed to rank the failure modes. A practical case study of the check valve is provided to validate the applicability of the proposed FMEA. Comparative studies demonstrate the efficacy of the proposed FR-MCGDM, with remarkable advantages in handling the uncertainty and subjectivity during failure modes evaluation. Graphical abstract: Highlights: A fuzzy rough number extended MCGDM is proposed for FMEA under uncertainty. A fuzzy rough number is presented to handle the uncertainty and subjectivity in FMEA. A fuzzy rough number extended AHP is developed to calculate the criteria weights. A fuzzy rough number extended VIKOR is proposed to determine the priority ranking. The objectivity of the failure mode evaluation is well enhanced.